2014
DOI: 10.1007/s12035-014-8864-9
|View full text |Cite
|
Sign up to set email alerts
|

Linking ATM Promoter Methylation to Cell Cycle Protein Expression in Brain Tumor Patients: Cellular Molecular Triangle Correlation in ATM Territory

Abstract: Ataxia telangiectasia mutated (ATM) is a key gene in DNA double-strand break (DSB), and therefore, most of its disabling genetic alterations play an important initiative role in many types of cancer. However, the exact role of ATM gene and its epigenetic alterations, especially promoter methylation in different grades of brain tumors, remains elusive. The current study was conducted to query possible correlations among methylation statue of ATM gene, ATM/ retinoblastoma (RB) protein expression, D1853N ATM poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…57 ATM protein belongs to PI3/PI4-kinase family and is an important cell cycle-checkpoint kinase reported as hypermethylated in human colorectal cancer cell lines, oral SCCs, breast cancers, and brain tumors. [58][59][60][61] In addition to this, methylation of ATM promoter is correlated with radiosensitivity in colorectal cancers. 59 FGF18 is a fibroblast growth factor family member possessing cell survival and mitogenic activities and is involved in cell growth, morphogenesis, tumor growth, and invasion by regulation of actin cytoskeleton, PI3K, and fibroblast growth factor receptor (FGFR) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…57 ATM protein belongs to PI3/PI4-kinase family and is an important cell cycle-checkpoint kinase reported as hypermethylated in human colorectal cancer cell lines, oral SCCs, breast cancers, and brain tumors. [58][59][60][61] In addition to this, methylation of ATM promoter is correlated with radiosensitivity in colorectal cancers. 59 FGF18 is a fibroblast growth factor family member possessing cell survival and mitogenic activities and is involved in cell growth, morphogenesis, tumor growth, and invasion by regulation of actin cytoskeleton, PI3K, and fibroblast growth factor receptor (FGFR) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, metastatic progression has been classified as a stepwise molecular alteration process of cancer development which requires three hits, D1853N, IVS38-63T>A, and IVS38-30A>G, occurring sequentially in astrocytes 152 ( Figure 4 ). In addition, Mehdipour et al 67 found a triangular correlation between methylation of the ATM promoter and protein expression of ATM with the D1853N variant. Evaluation of the D1853N variant alongside other alterations in patients with breast cancer, particularly those with breast to brain metastases, could lead to development of appropriate clinical management approaches.…”
Section: Breast To Brain Metastasesmentioning
confidence: 99%
“…These observations are comparable with the high expression levels of p53 and ATM proteins in healthy individuals. Interestingly, low levels of ATM protein expression, together with clones of cells with low levels of Rb protein, indicate a harmonic expression pattern in astrocytoma tumors 67 . …”
Section: Cell-cycle Checkpoint Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, four samples with wt ATM allele had either none (P12, P13, P16) or borderline (P15) levels of p53-Ser15 phosphorylation after IR, suggesting defective ATM/p53 pathway. Whether this apparent nonfunctionality of ATM in wt/del ATM samples is due to an involvement of other factors impacting on the expression and activity of ATM [12] or due to a possible epigenetic silencing of ATM expression known in various types of cancer [13] remains to be determined.…”
mentioning
confidence: 99%